COGNITIVE GRAMMAR IN AN ENGLISH CLASSROOM, OR, HOW TO MAKE LIFE FOR RUSSIAN STUDENTS EASIER - A. V. Kravchenko (Vestnik MGIMO-Universiteta, 2013)
Every EFL teacher who teaches native speakers of Russian knows that the main roadblocks encountered in the classroom pertain to acquisition of articles, prepositions, and grammatical forms of the verb. With regard to articles, the situation is clear: as there are none in Russian, the student needs to understand their role and function in English. It's a bit different with prepositions: even though there are prepositions in Russian, their number and usage in English very often cause confusion. Finally, as far as the so-called tenses go – which are, in fact, tense-aspect forms – many students experience difficulties in developing necessary skills for a simple reason. Being used to the three tenses in Russian (the present, the past, and the future), they are often incapable of understanding the organizational and functional logic of a system which comprises twelve forms in the active voice. With this in mind, the problem of tense acquisition is shown to be rooted in inadequate metalinguistic knowledge pertaining to the meaning and function of the categories of tense and aspect in Russian. Since cognitive structures underlying these grammatical categories are grounded in perceptual experience and are similar in both languages, a cognitive approach, by using the native language as scaffolding, allows the student to benefit from a simple algorithm for choosing a tense in discourse. This radically facilitates grammar acquisition, eliminating many imaginary difficulties. The described approach to instructed tense–aspect acquisition has been successfully used by the author and his disciples and colleagues in educational institutions of different levels for over twenty years, proving to be much more efficient than traditional techniques.